Predatory efficacy of toxorhynchites amboinensis doleschall(Diptera: culicidae: toxorhynchitinae) on aedes spp. (Diptera: culicidae:culicinae) larvae. - Digma, Jonathan R. (2013)
ABSTRACT see Upload (MT BIO 062 2013)